Self-Regulated Learning dalam Pembelajaran Digital: Studi Kualitatif Tentang Tantangan Dan Strategi Siswa SMP - Faruq, Faruq (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2026)
Digital learning requires students to possess strong Self-Regulated Learning (SRL) skills in order to manage their learning processes independently. This study aims to explore the challenges and strategies of self-regulated learning among junior high school students in the context of digital learning. The study employed a qualitative descriptive approach with a case study design. The participants consisted of two seventh-grade junior high school students who engaged in digital learning and were selected using purposive sampling. The object of the study was students’ experiences in applying self-regulated learning during digital learning activities. Data were collected through in-depth interviews and analyzed using thematic analysis. The findings identified six main themes in students’ SRL practices, namely learning planning, learning strategies, learning outcomes, emotional experiences during learning, social support, and learning barriers. The results indicate that students with stronger SRL skills tend to be able to develop structured study schedules, apply learning strategies appropriate to the learning materials, and achieve more optimal learning outcomes. Social support from parents and peers also plays an important role in supporting successful digital learning, while digital distractions and limited interaction with teachers remain major challenges. This study highlights the importance of strengthening students’ self-regulated learning through pedagogical support and adaptive learning environments in digital learning contexts.